'Converse racialization' and 'un/marking' language: The making of a bilingual university in a neoliberal world. (June 2021) - Mena, Mike; García, Ofelia
Abstract: The discourse on the opening of a bilingual university along the Texas-Mexico border leads us to propose a theory of 'converse racialization' through which the local Spanish is being progressively 'unmarked' and disassociated from the language practice of Mexican Americans. Converse racialization, as the equal and opposite co-constituting underside of racialization, shifts the directionality of semiotic indexes away from a particular 'race' or 'ethnicity' (including whiteness) and produces an apparent state of 'unmarkedness'. We argue that the process of 'unmarking' Spanish has social, economic, and racializing consequences. Specifically, the language-as-resource discourse obscures and rearticulates the 'deficiency perspective' that continues to perpetuate structural inequalities that Latinxs in the border face. (Racialization, higher education, critical race theory, bilingualism, neoliberalism)*